2018
DOI: 10.5056/jnm17021
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling and Assessment of Vitamin D and Serotonin Pathway Variations in Patients With Irritable Bowel Syndrome

Abstract: Background/AimsIrritable bowel syndrome (IBS) is a multifaceted disorder that afflicts millions of individuals worldwide. IBS is currently diagnosed based on the presence/duration of symptoms and systematic exclusion of other conditions. A more direct manner to identify IBS is needed to reduce healthcare costs and the time required for accurate diagnosis. The overarching objective of this work is to identify gene expression-based biological signatures and biomarkers of IBS. MethodsGene transcripts from 24 tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…Further studies are needed on the role of threonine in IBS‐D. Tryptophan, which is converted to serotonin, is known to be associated with IBS, as the increased serotonin levels lead to increased GI motility and visceral hypersensitivity . Previous studies have shown that patients with IBS‐D have comparatively higher levels of free serum tryptophan than those in HC .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed on the role of threonine in IBS‐D. Tryptophan, which is converted to serotonin, is known to be associated with IBS, as the increased serotonin levels lead to increased GI motility and visceral hypersensitivity . Previous studies have shown that patients with IBS‐D have comparatively higher levels of free serum tryptophan than those in HC .…”
Section: Discussionmentioning
confidence: 99%
“…TPH2 knockout mice show intestinal dysmotility. Serotonin dysregulation, secondary to vitamin D deficiency, has been linked to Inflammatory bowel syndrome [ 41 ] and inflammatory bowel disease [ 99 , 100 ]. It is possible that serotonin is the common mediator in the changes seen in each of these conditions.…”
Section: Gut Microbiota and Neurotransmitters In Autism Spectrum Disomentioning
confidence: 99%
“…A previous small bowel mucosal gene expression study has reported that both transcriptome expression and immune-related mechanisms are altered in IBS-D patients ( 27 ). Another DNA microarray analysis has demonstrated that IBS is associated with abnormal serotonin metabolism and vitamin D deficiency ( 28 ). Currently, most omics studies only report the observational results of IBS-related differentially expressed genes (DEGs).…”
Section: Introductionmentioning
confidence: 99%